Psychological hardiness and its relationship to health awareness Among Kurdish people in Kurdistan Region during the pandemic of Covid-19 - Mohammed, Trifa Murad; Mohammedhkan, Hanaw Hasan; Qader, Delan Jamal (Kurdistan Journal of Applied Research, 2021)
Objective: Like Iraq and neighboring countries, the Kurdistan region was affected by the epidemic which gradually led to a lockdown in March and April and a wide-spread disruption of people’s life and activates. In this study, the researcher investigated the psychological hardiness and its relation to health awareness among citizens of the Kurdistan region during the Corona epidemic. Methods: This study followed a cross-sectional design quantitative survey that was conducted online from 1 to 18 April 2020. After two months of lockdown due to coronavirus pandemic in the Kurdistan Region. A questionnaire of 25 questioners to measure psychological hardiness, later the researchers got the psychometric qualities. Results: The researcher observed high psychological hardiness levels in the study, because of the Covid-19 pandemic. It has shown the non-significant association between psychological hardiness and health awareness and identified several significant factors associated with this psychological hardiness and health awareness. Conclusion: Using contractive tools, the study showed that the psychological hardiness of the citizens of the Kurdistan region is at a low level during the COVID-19 pandemic. The results could serve as a framework for future research to examine the influence of the pandemic on the population’s association of psychological hardiness with health awareness.